RATIONALE DESIGN MEASURES TO ENSURE THE RELIABILITY OF HIGH-RISE BUILDINGS IN PROGRESSIVE COLLAPSE (Academic journal Industrial Machine Building Civil Engineering, 2017)
The results of studies on the justification of design solutions ensure reliable designs atprogressive collapse were presented. Analysis of the stress-strain state of the structures wasperformed using software package «Lira 9.6». The most effective amount of stiffeningdiaphragms to ensure the reliability of the building was determined. The features of theimpact on the reliability of the floor structure of the building was determined. The results ofevaluation of the stability of columns of different types to explosive impact were presented.Keywords: progressive collapse, reliability, reinforced concrete structures, compositestructures, columns, diaphragm stiffness, finite element method.